Learning in Sustainable Agriculture: Food Miles and Missing Objects. (1st May 2005) - Iles, Alastair
Industrial production imposes geographical, economic and cultural distances between producers and consumers. The concept of constituting 'missing objects' can help shrink these distances by enabling actors to engage in discourses and practices about contexts beyond what is materially present. Since the mid-1990s, food miles have emerged as an example of missing objects, representing the distance that agricultural products travel from the farm to the dining table, and the environmental effects of transportation. I analyse how consumers, farmers, activists, industry and policy-makers in the United States and Europe are building agency in making and using food miles.